FILM DOKUMENTER GERAKAN MEREKAM KOTA KARYA GRESIK MOVIE: TELAAH SEMIOTIKA JOHN FISKE - Utomo, Khoirul Dodi; Jupriono, Jupriono; Ayodya, Beta Puspitaning (Universitas 17 Agustus 1945 Surabaya, 2018)
The Background of this research begins from the existence of a â€œMovement Record the Cityâ€. Movement which was initiated by Gresik Movie aimsto invite the Gresi community to participate in maintaining the sustainability of the city by recording anything that has artistic and historical value in the city of Gresik. Considering that many other things that continue to dissaper and change from the city of Gresik make the Gresik Movie community want to invite the public to preserve this beloved city. Before itâ€™s too late and become the story, would that to answer the formulation issue in this study that was message contained in the documentary video â€œMovement Record the Cityâ€ the work of Gresik Movie. A theory used n ths study s the theory of semiotics of the social codes of television John Fiske. Research method, the type of research used was qualitative descriptive study, the primary data source in the form of the original video â€œMovement Record the Cityâ€ obtained from the Gresik movie youtube channel. The results showed that the meaning of the government Gresik more likely to use the ideology of capitalism, it is supported by the many of existing developments un the city of Gresik. But the government Gresik another thing about the ideology indeed Gresik cling to region, this is demonstrated by the many of development of the industrial sector and forget the religious development. The change in orientation of the community and the regional government of Gresik was criticalized and reminded of the way â€œthe video was removedâ€. This disappearance represent the power of domination of business investors and industry players who are doing development in the industrial sector as well as bullying the religious culture of santri.Keyword: semiotic, ideology, culture